Significant implication of unified power quality conditioner in power quality problems mitigation - Hasan, Kamrul; Othman, Muhammad Murtadha; Rahman, Nor Farahaida Abdul; Hannan, M. A.; Musirin, Ismail (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents an analysis of a three-phase unified power quality conditioner (UPQC) in terms of design and performance. A back to back connection of a series compensator and a shunt compensator with a common DC-bus is utilized to build the UPQC model. The series compensator compensates the power quality problems such as grid voltage sags/swells for the grid side. During sag and swell condition, the compensated voltage is injected by the series compensator in phase with the point of common coupling (PCC) or out of phase with PCC. The load current harmonics is compensated by using the shunt compensator. The dynamic performance and  the steady state of the designed model are analyzed by using MATLAB-Simulink under several disturbances such as PCC voltage harmonics, voltage sags/swells and load unbalancing using a nonlinear load.